Membuat Linux Distro dengan SLAX - Susi Rianti (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2015)
Lack of understanding of the operating system as well as the dependence on a specific vendor , underdevelopment of creativity of the nation.So to improve the creativity and eliminate dependence on certain vendors then use Linux. Linux is an operating system open souce, portable, small size and bootable. Linux used is Linux Slax